Saudi-Japanese relations1938-1973(historical study - Joudah Sabih Al-Maliki, Ali; Dawood Salman Al-Shallal, Faraqed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Japan is one of the countries that suffer from a severe shortage in its economic resources ,especially oil .therefore ,it turned its attention towards the kingdom of Saudi Arabia for possessing oil wealth and granted the kingdom several oil concessions to japan to avoid western companies monopolizing its oil .the kingdom ranked first in the purchase of Japanese manufactured goods during the fifties and sixties of the century the past ,but Saudi-Japanese relations were greatly strained to the Arab oil embargo in1973 and relations between the two countries did not improve until after japan fully supported the rights of the Palestinian people.